PENINGKATAN PENGAWASAN TERHADAP PROSEDUR PEMBERIAN PEMBIAYAAN MODAL USAHA PADA KOPERASI JASA KEUANGAN SYARI’AH (KJKS) AL-ANSHARI BUKITTINGGI - Kevry Ramdany (Ensiklopedia of Journal, 2020)
The study on "Improving Oversight of Procedures for the Provision of Business Capital Financing in Sharia Financial Services Cooperatives (KJKS) Al-Anshari Bukittinggi" was carried out from February 22 to April 31, 2012, with the aim of obtaining an overview of the supervision of procedures for providing capital financing business in KJKS Al-Anshari Bukittinggi located on Jalan Jenderal Sudirman No. 27-29 Bukittinggi. The research method used in this research is descriptive method, the data is taken through a survey technique using a list of questions (questionnaire) and interviews relating to increased supervision of the provision of business capital financing procedures that have been prepared, then proceed with field studies, library studies and analysis . From the research conducted, it was obtained that the increase in supervision over the procedures for providing business capital financing carried out by KJKS Al-Anshari Bukittinggi in general had been going well according to the terms and conditions in force.